Legal Aspects of the Use of Artificial Intelligence for Medical Diagnosis Under Law No. 17 Of 2023 on Health and Law No. 27 Of 2022 on the Protection of Personal Data - Putu Aditya Sukarendra; Linawati Linawati; I Gusti Ayu Putri Kartika (Indonesian Journal of Global Health Research, 2026)
Health is a fundamental human right guaranteed by various international and national legal instruments, including the 1945 Constitution and Law No. 17 of 2023 on Health. The state has a responsibility to provide adequate health facilities and services to achieve the optimal level of public health. With the development of information technology, innovations such as Artificial Intelligence (AI) are beginning to be utilized in the health sector, particularly in medical diagnosis, as they can improve the accuracy and efficiency of services.The use of AI in medical diagnosis is supported by regulations that encourage health technology innovation, yet it also poses various challenges, particularly regarding ethical considerations, trust, accountability, and the protection of patients’ personal data as stipulated in Law No. 27 of 2022. Additionally, the use of AI requires proper risk management to uphold the principles of fairness, transparency, and security.Although regulatory frameworks related to health, technology, and data protection are in place, specific regulations regarding the use of AI in medical diagnosis remain unclear and incomplete. This creates legal uncertainty, particularly regarding liability in the event of a misdiagnosis. Therefore, the development of more detailed regulations is necessary to provide legal certainty and ensure that the use of AI in healthcare services is safe, ethical, and responsible. This study aims to explore the legal aspects of the use of Artificial Intelligence (AI) in medical diagnosis, in light of Law No. 17 of 2023 on Health and Law No. 27 of 2022 on Personal Data Protection. Patient data is a valuable asset that is not only sensitive but also vulnerable to misuse. The integration of AI in diagnosis requires access to large amounts of patient data to train algorithms and improve diagnostic accuracy. This study falls under the category of normative legal research, which focuses on legal norms found in legislation, legal doctrine, and other relevant regulations. It analyzes the legal framework, expert opinions, and relevant case studies to assess how AI can be integrated into the healthcare system while ensuring compliance with data protection regulations and safeguarding patients’ rights. This study investigates the implications of these laws on AI applications in medical diagnostics, with a focus on data security, patient consent, and the ethical use of AI in healthcare. It also examines how AI developers and healthcare providers must navigate these regulations to ensure privacy and transparency. The findings reveal that while this legislation provides a strong foundation for data protection in AI-based healthcare, challenges remain in its implementation.